Optimizing Human Potentials in Islamic Education: Senses, Aql, and Qalb - Fitri Meliani; Nurwadjah Ahmad; Andewi Suhartini (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2023)
God created man in both physical and spiritual aspects. The physical part is the human body that can be seen like the senses, while the spiritual aspect is aql and qalb, which are invisible. This research analyzes human potential based on Qur'anic terminology and its role in Islamic education. This research used qualitative methods. The data collection was documented from the Qur'an interpretation as the primary data source and journal articles and renowned books related to the topics as the secondary data sources. Data analysts used text analysis methods, such as selecting critical terms from the vocabulary of the Qur'an interpretation, determining the basic meaning and relational meaning, and inferring and integrating these concepts into one general idea. The results of this study are. First, the potential of sense was mentioned in the Qur'an in three terms: Al-Sam'u is repeated 185 times, Al-Bashr is repeated 139 times, and Al-Dhuq, is repeated 48 times. Second, the potential of reason, etymologically, the term aql is mentioned in the Qur'an in more than 49 words, collected in dzakara, faqiha, 'alima, tadabbara, tafakkur, and ulul albab. Third, the potential of the qalb (heart), the mashdar form of the qalaba-yaqlibu-qalban root, which means true. The Qur'an uses the word heart mentioned 122 times, spread across 45 letters and 112 verses. Islamic education must covers all potentials such as tarbiyah imaniyah, tarbiyah khuluqiyah, tarbiyah jismiyah, tarbiyah aqliyah, nafsiyah ijtima'iyah, so it will produce quality Islamic education output.